The productivity growth slowdown in advanced economies: Causes and policy recommendations - Marcin Wrónski (International Journal of Management and Economics, 2019)
The growth of total factor productivity (TFP) in advanced economies has slowed significantly after the 1970s. The global financial crisis (GFC) has resulted in the second productivity growth slowdown. This paper, on the basis of a broad literature review, identifies the structural forces and legacies of the financial crisis, explaining the productivity growth slowdown and providing possible policy solutions. The mismeasurement hypothesis is also discussed. The slowing pace of innovations, population aging, slowing human capital accumulation, limits of structural transformation, capital misallocation, and firm-level factors are identified as structural forces slowing TFP growth. Lack of capital deepening, financial frictions, and slowdown of international trade are the most important legacies of GFC affecting productivity growth.
Keywords: D24; E01; E24; O47; 650; macroeconomics; productivity; TFP; productivity growth slowdown